The Combination of Gastroschisis, Jejunal Atresia, and Colonic Atresia in a Newborn - Zachary Bauman; Victor Nanagas (Case Reports in Pediatrics)
We encountered a rare case of gastroschisis associated with jejunal atresia and colonic atresia. In our case, the jejunal atresia was not discovered for 27 days after the initial abdominal wall closure. The colonic atresia was not discovered for 48 days after initial repair of the gastroschisis secondary to the rarity of the disorder. Both types of atresia were repaired with primary hand-sewn anastomoses. Other than the prolonged parenteral nutrition and hyperbilirubinemia, our patient did very well throughout his hospital course. Based on our case presentation, small bowel atresia and colonic atresia must be considered in patients who undergo abdominal wall closure for gastroschisis with prolonged symptoms suggestive of bowel obstruction. Our case report also demonstrates primary enteric anastomosis as a safe, well-tolerated surgical option for patients with types of intestinal atresia.